2021
DOI: 10.1093/neuros/nyab365
|View full text |Cite
|
Sign up to set email alerts
|

Flow Diversion for Middle Cerebral Artery Aneurysms: An International Cohort Study

Abstract: BACKGROUND Open surgery has traditionally been preferred for the management of bifurcation middle cerebral artery (MCA) aneurysms. Flow diverting stents present a novel endovascular strategy for aneurysm treatment. OBJECTIVE To add to the limited literature describing the outcomes and complications in the use of flow diverters for the treatment of these complex aneurysms. METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…DWI lesions were more prevalent in patients who underwent p64 MW HPC implantation for MCA/MCA-bifurcation aneurysms. By contrast, the results of a systematic review and metaanalysis published by Bond et al [18] revealed that DWI lesions developed in up to 67% of patients presenting with IAs after FD implantation. Silent ischemic events were reported in as many as 50.9-90% of cases involving the implantation of the uncoated Pipeline FD [21][22][23][24].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…DWI lesions were more prevalent in patients who underwent p64 MW HPC implantation for MCA/MCA-bifurcation aneurysms. By contrast, the results of a systematic review and metaanalysis published by Bond et al [18] revealed that DWI lesions developed in up to 67% of patients presenting with IAs after FD implantation. Silent ischemic events were reported in as many as 50.9-90% of cases involving the implantation of the uncoated Pipeline FD [21][22][23][24].…”
Section: Discussionmentioning
confidence: 87%
“…These findings represent a significant improvement over previously published data on the use of FD devices for MCA aneurysms. For example, (Aguilar) Pe ´rez et al [13] and Diestro et al [18] reported postprocedural complication rates of 15% and 16.7%, respectively, in patients with MCA-bifurcation aneurysms. However, we recognize that patients with an anticipated higher risk for ischemic complications were treated daily with subcutaneous LMW heparin for 4-6 weeks after FD treatment to reduce the risk of ischemic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Cagnazzo et al found 20% treatment-related complications with half of them having permanent clinical sequelae in an earlier study [ 43 ]. Diestro et al reported 16% thromboembolic complications after FD of the proximal MCA bifurcation in a collective of patients who required retreatment after a failed first surgical or endovascular attempt [ 44 ]. Contrary to that, Salem et al found that MCA-bifurcation aneurysms are treatable with much lower complication rates, the outcomes of their study being comparable to other, well consented FD locations [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis reported by Cagnazzo et al ( 22 ), focused on the use of FDDs in MCA aneurysms, showed that the overall rate of complete/near-complete occlusion during follow-up was 78.7% (95% CI: 67.8%–89.7%) with a 12-month median duration, and the rate of treatment-related complications was 20.7% (95% CI: 14%–27.5%) of which approximately 10% was permanent. More recently, Diestro et al ( 23 ) published an international cohort study of 54 MCA bifurcation aneurysms compared to the published series on open surgical treatment; FDDs have inferior outcomes and are associated with a higher rate of complications. In this report, 16.7% (9/54) of the patients suffered a thromboembolic complication, and from the 45 aneurysms with available follow-up data, 20% did not have adequate occlusion with a median follow-up time of 12 months.…”
Section: Discussionmentioning
confidence: 99%